ISBAR: Adding an extra step in handoff communication: A Review - Jadhav, Vaishali; Mahajan, Natasha (Indian Journal of Nursing Sciences, 2024)
Poor communication can harm patients or make work life difficult. Incident and complaint data provide strong evidence for the critical role of lack of appropriate communication in adverse events. The imperative to act to improve clinical communication is recognized by international agencies. Research has shown that using a standardized format can assist the transfer of information, particularly when there are time constraints. ISBAR (Introduction, Situation, Background Assessment, Recommendation) is such a tool. ISBAR organizes a conversation into the essential elements in the transfer of information from one source to another. Its effectiveness has been demonstrated in both clinical and non clinical situations of communication transfer. The present review discusses different studies related to ISBAR.